Inputs, Incentives, and Self-Selection at the Workplace - Francesco Amodio; Miguel A. Martinez-Carrasco (Institute of Labor Economics (IZA), 2019)
This paper studies how asymmetric information over inputs affects workers' response to incentives and self-selection at the workplace. Using daily records from a Peruvian egg production plant, we exploit a sudden change in the worker salary structure and find that workers' effort, firm profits, and worker participation change differentially along the two margins of input quality and worker type. Firm profits increase differentially from high productivity workers, but absenteeism and quits of these workers also differentially increase. Evidence shows that information asymmetries over inputs between workers and managers shape the response to incentives and self-selection at the workplace.
Keywords: D22; D24; J24; J33; M11; M52; M54; O12; 330; asymmetric information; input heterogeneity; incentives; self-selection